Aggregation‐Induced Emission Properties of Copper Iodide Clusters. Issue 18 (28th August 2019) - Utrera‐Melero, Raquel; Mevellec, Jean‐Yves; Gautier, Nicolas; Stephant, Nicolas; Massuyeau, Florian; Perruchas, Sandrine
Abstract: The aggregation‐induced emission (AIE) properties of two different copper iodide clusters have been studied. These two [Cu4 I4 L4 ] clusters differ by their coordinated phosphine ligand and the luminescent mechanochromic properties are only displayed by one of them. The two clusters are AIE‐active luminophors that exhibit an intense emission in the visible region upon aggregation. The formed particles present luminescent thermochromism comparable to that of the bulk compounds. The observed AIE properties can be attributed to suppression of nonradiative relaxation of the excited states in a more rigid state, in relation to the large structural relaxation of the excited triplet state. The differences observed in the AIE properties of the two clusters can be related to the different ligands. A correlation between the luminescence mechanochromic properties and the AIE effect is not straightforward, but the formation of "soft" molecular solids is a common characteristic that can explain the photoactive properties of these compounds. Abstract : Revealing relationships : The aggregation‐induced emission (AIE) properties of two cubane copper iodide clusters have been studied in light of their photoactive properties (see figure). A correlation between the luminescence mechanochromic properties and the AIE effect is not straightforward, but the formation of "soft" molecular solids is a common characteristic that can explain the photoactive properties of these compounds.